2022
DOI: 10.37939/jrmc.v26i1.1824
|View full text |Cite
|
Sign up to set email alerts
|

Improving Medical Students’ Learning Experience of Pathology by Online Practical Sessions through Virtual Microscopy

Abstract: ABSTRACT: Objective: To assess the impact of interactive virtual pathology slides on students’ understanding of pathological disease processes. Materials & Methods: The study was conducted at Shifa College of medicine, Islamabad. Class of 3rd year MBBS, comprising of 111 students, was divided into two groups during two teaching modules. All students received online lectures prior to practical sessions. In the first module, one group was taught virtual slides through online interactive sessions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Development of diagnostic and practical skills during laboratory sessions was an important finding [33,39,48,53,56,58,59,64]. Studies also reported that VM promotes selfdirected learning [31,35,38,41,48,58,59,64] and thus an overall better method of learning for exam preparation for the students [32,38,52,53,56].…”
Section: Vm Podcastmentioning
confidence: 99%
See 4 more Smart Citations
“…Development of diagnostic and practical skills during laboratory sessions was an important finding [33,39,48,53,56,58,59,64]. Studies also reported that VM promotes selfdirected learning [31,35,38,41,48,58,59,64] and thus an overall better method of learning for exam preparation for the students [32,38,52,53,56].…”
Section: Vm Podcastmentioning
confidence: 99%
“…Improved student and faculty rapport [33,34,42,45,51,52,56,60] as well as better cooperation and participation amongst students was another interesting finding [20,[31][32][33][34]36,43,52,57,60,61,66,67].…”
Section: Vm Podcastmentioning
confidence: 99%
See 3 more Smart Citations